[Members of the Senior Class of 1909 after planting the Class Tree] - Frank Aston::::::photographer::: (1909)
Members of the Senior Class of 1909 after planting the Class Tree. Left to Right: Hazel May Griffith, --, --, --, Rachael E. Ramage, George Albert Tilton. (Addressed to Miss Hazel Griffith, signed 'Geo. A. Tilton, Jr.'; card appears to have been passed on to someone else with note added by another person 'T.F.' or 'J.F.')